Efeitos do óleo essencial do Eucalyptus tereticornis e dos constituintes 1,8-cineol, α-pineno e β-pineno na motilidade do músculo liso gastrintestinal de ratos - Jucá, Davi Matthews (2012)
The monoterpenes 1,8-cineole, α-pinen and β-pinene are constituents commonly found in several essential oils obtained from plants in Brazilian northeast such as “malva-santa” and “eucalipto” (Essential Oil of Eucalyptus tereticornis - EOET), which are used in folk medicine to treat respiratory and gastrointestinal dysfunctions. Myorelaxant actions are due to the presence of these constituents in their essential oils. The present work aimed to further study the pharmacological effects of these compounds, as well as the EOET, on smooth muscle gastrointestinal contractility and the prokinetic effect in rats. Wistar rats (200-250 g) were used, sacrificed by cervical dislocation. Strips were carefully obtained from gastric fundus, duodenum and ileum, and were maintained in normal Tyrode‟s solution. Isometric contractions were recorded through force transducers coupled to a computerized data acquisition system. Solutions containing 1,8-cineolo, α-pinene or β-pinene were prepared with Tween 80 (final concentration ≤ 0,2% v/v). Solely used, EOET, 1,8-cineole, α-pinene or β-pinene decreased duodenal basal tonus. In basal tone of gastric fundus isolated strips, EOET and 1,8-cineole had relaxant effect, while α-pinene and β-pinene had contractile effect. This contractile effect of α-pinene and β-pinene in isolated strips of gastric fundus is due to possible interference with IP3-dependent mechanism and independent of the muscarinic receptor activation and a central action in the activation of nicotinic receptors, in the same way, the duodenal smooth muscle relaxant effect is mediated by possible interference with the cellular mechanisms mediated by the formation of IP3. Moreover, as shown above, in the rat ileum, monoterpenes activate capacitative Ca2+ entry to intracellular milieu after Ca2+ stores depletion. The α-pinene and β-pinene also accelerated intestinal transit and reduced gastric compliance. Our data show that OEET has prokinetic properties in rats, which may be attributable to the contrasting effects induced by α-pinene and β-pinene, corroborating data presented previously (Jucá, 2007).